The impact of foreign direct investment on the level of unemployment in Sudan During the period (1990- 2014 - د. عبد الرحمن عبد الله كبسور (White Nile Journal for Studies and Research, 2020)
in This study aims to investigate the impact of Foreign Direct Investment on the unemployment rate in the Sudan, it aimedatidentifying the extent of foreign direct investment contribution in reducing unemployment. The study addressed the problem in the following question: Whatis the extent of foreign direct investment contribution reducingunemployment in the Sudan? The studyrelied on a descriptive and analyticalapproach, in addition to the use of statisticalmethods and programs, including Eviews program to study the relationshipbetweenforeign direct investment and unemployment rates in the Sudanduring the studyperiod. The study found out that foreign investment leads to increased unemployment in the Sudan because the foreign investors and institutional investors using foreign staff and workers of the country to work in investment projects in Sudan, And educational policies in Sudan are not compatible with the labor marketrequirements. The study recommendsthe following: the Sudanese Ministry of Investment should consider with respect to operating and employment in foreign investment projectswhere the study showedthatforeign direct investment increase sunemployment in the Sudan, and the need for coordination between the Ministry of Higher Education and Ministry of Labour to be made the educational policies and curricula keep pace with the requirements of the labormarket in Sudan.